Strategi perbaikan makanan khas betawi gabus pucung melalui pendekatan importance performance analysis dan causal loop diagram - Ervina Mela; Yasmina Syafiya; Retno Setyawati (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Some regional specialties are at risk of being abandoned by the community. One of them is gabus pucung, a traditional Betawi dish, which requires efforts to maintain its existence. The aim of this research is to identify the attributes that need improvement in gabus pucung based on consumer perceptions and then formulate improvement strategies. Data was collected through a questionnaire distributed to 100 respondents and processed using Importance-Performance Analysis and Causal Loop Diagrams. The findings indicate that four attributes of gabus pucung cuisine require improvement: taste, promotion via social media, promotion through events/exhibitions, and restaurant cleanliness. To enhance food taste, a recommended strategy is to standardize recipes. The strategy for improving promotion via social media involves increasing online engagement. To address challenges in exhibitions, restaurant entrepreneurs can reduce serving times and offer smaller portion options. Another exhibition-related strategy is to involve corporate CSR programs to support MSME entrepreneurs specializing in regional cuisine through exhibition activities. The recommended improvement strategy for restaurant cleanliness is implementing SSOP (Sanitation Standard Operating Procedures). This research is expected to have a positive impact on the preservation of Indonesian culture and the economy by creating jobs and increasing income, especially in the culinary tourism sector.